The Remote Leadership Paradox: Mitigating Employee Burnout and Enhancing Organizational Citizenship Behavior through Digital Transformational Leadership - Sota Yamamoto; Haruka Sato; Ethan Tan (Research Psychologie, Orientation et Conseil, 2025)
The shift to remote work has introduced significant challenges for leaders, particularly in balancing the need for organizational efficiency with the well-being of employees. The paradox of remote leadership lies in the difficulty of mitigating employee burnout Tan, Ewhile enhancing organizational citizenship behavior (OCB) through effective leadership. This study explores the relationship between digital transformational leadership, employee burnout, and OCB in remote work environments. The primary aim of this research is to investigate how digital transformational leadership can reduce employee burnout and promote OCB in remote work settings. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. The survey assessed employee burnout, OCB, and perceptions of digital leadership, while interviews provided deeper insights into employee experiences. The findings reveal that digital transformational leadership significantly reduces burnout and enhances OCB. Employees who reported higher levels of leadership support and empowerment in virtual environments experienced lower burnout levels and higher engagement in extra-role behaviors. The study emphasizes the importance of digital leadership practices in fostering a healthy, motivated, and productive remote workforce. In conclusion, digital transformational leadership is essential for navigating the remote leadership paradox.